Novel Biomarkers with Potential Utility in Diagnosis of liver Fibrosis - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Liver fibrosis, which is a consequence of chronic liver diseases, is associated with excessive deposition of extracellular matrix (ECM) proteins during the dynamic process of repair and regeneration. Hence the events associated with repair and regeneration could be explored as predictable markers to assess liver fibrosis. We report here the possible utility of a few biomarkers in early diagnosis of liver fibrosis.
Keywords: Liver fibrosis; Biomarker; Chronic liver disease; Non-invasive diagnosis; Diagnostic imaging